The Association between Asthma and Obesity in Children -1 Inflammatory and Mechanical Factors - Valentina Cvejoska-Cholakovska; Mirjana Kocova; Vesna Velikj-Stefanovska; Emilija Vlashki (ID Design / Scientific Foundation Spiroski, 2019)
BACKGROUND: Association of asthma and obesity has been demonstrated in numerous epidemiological studies. However, the underlying mechanisms of the association are not well understood. Both conditions are characterized by chronic tissue inflammation, which includes numerous different inflammatory markers, and possible atopy. AIM: The study aimed to investigate the association between asthma and obesity in children and assess several of potential underlying mechanisms, including the parameters of systemic inflammation (CRP, fibrinogen) and the mechanical effect of obesity on the respiratory system through parameters of lung function. An additional aim was to examine the role of atopy in overweight children with asthma and to investigate the type of respiratory inflammation. MATERIAL AND METHODS: This prospective study included 72 patients in the age group of 7-15 years, including 38 with high body mass index (BMI), 16 with asthma and normal BMI, and 18 with asthma and high BMI for sex and age. Non-specific inflammatory markers (fibrinogen, CRP), eosinophilia, and total serum IgE were investigated. The patients underwent a skin prick test (SPT) with standard inhalant allergen extracts, measurement of fractional exhaled nitric oxide Fe (NO), and an assessment of lung function. RESULTS: In overweight groups of children we determined significantly higher values (p < 0.001) of both acute inflammatory reactants, CRP and fibrinogen, with no difference between children with and without asthma. There was a significant increase in eosinophilia, total IgE, and positive SPT in the asthmatic groups compared to the group of non-asthmatic patients (p < 0.001 for the three parameters). Compared to the group composed of overweight patients without asthma, the asthmatic patients had higher NO values (p < 0.001). No significant difference in the lung function parameters was found between the three groups (p > 0.05). CONCLUSION: A positive association between asthma and obesity with inflammation as an underlying mechanism, eosinophilic one in asthmatic patients and non-eosinophilic one in overweight patients, was determined. It seems that the lung function parameters did not differ between asthmatic patients and overweight patients. No influence of atopy in the association between asthma and obesity was verified. Further analyses of specific inflammatory markers, for an in-depth evaluation of the mechanisms leading to the association of obesity and asthma, are warranted.
Keywords: Asthma, Body mass index, Children; Body mass index; Children; overweight